Analysis of the spatio-temporal evolution of iron ore trade from a geopolitical perspective: A complex network model - Shengzhong Huang; Chenrui Cai; Bo Fu (PLoS ONE, 2026)
Iron ore is the primary raw material for steel production, and the steel industry is a fundamental pillar of the national economy. Given the increasing strategic importance of iron ore, this paper introduces a complex network model to analyze the evolution characteristics of the global iron ore trade pattern from 2000 to 2023, aiming to assess the trade situation of iron ore. In addition, relevant policies have been formulated to ensure the stable supply of iron ore. The study shows that the Global Iron Ore Trade Network (GIOTN) is active and efficient. However, the iron ore trade is highly imbalanced and heavily influenced by geopolitical factors. Furthermore, under the impact of geopolitics, there is a gradual shift from resource dominance to capital dominance in the global iron ore trade. In terms of trade competition, relations between Europe and Brazil seem to be more intense, and the competitive landscape of iron ore trade in southern Africa is becoming increasingly prominent. Meanwhile, the global iron ore trade is becoming more regionalized due to geopolitical influences, with trade communities trending towards smaller and more balanced states. Emerging economies such as China, South Africa, and India are playing an increasingly important role in the global iron ore trade.